Security System Load Reduction in SDN - Lee, Ye Won; Lee, Chae Woo (Journal of Korean Institute of Communications and Information Sciences, 2021)
The recent trend of SDN has been demonstrated for security systems such as Intrusion Detection System and Intrusion Prevention System have been introduced in the SDN environment to increase network security. However, the load on the security system increased by examining all packets, and various packet sampling-based techniques were proposed to solve this problem, but there were still problems with the security system being high or the network security was poor due to the sampling techniques. In this paper, we propose a system improving security and reducing system loads through management table-based packet management in case of flooding attack. The existing system is inspected by backlog queue value but the proposed security system can be flexibly executed for each packet creating a management table. This table is based on the time difference between packets and the frequency of occurrence of packets. The load on the security system can be reduced by blocking the corresponding packet by the controller for a certain period of time when abnormal packet comes. As a result of the performance evaluation of the proposed method, it is confirmed that the load of the security system is improved by about 25% compared to the existing system.
Keywords: Flooding; IDS; SDN